A joint analysis of determinants and performance consequences of ambidexterity - Eva M. Pertusa-Ortega; José Francisco Molina Azorín (BRQ Business Research Quarterly, 2018)
Summary This paper simultaneously analyzes antecedents and consequences of organizational ambidexterity. Regarding antecedents, the paper examines the influence of internal antecedents (organizational structure) and external antecedents (environmental dynamism). With regard to consequences, the paper analyzes the impact of ambidexterity on firm performance. Moreover, we use two different approaches to ambidexterity (structural and contextual perspectives). The findings show that a hybrid organizational structure, with organic (decentralization) and mechanistic characteristics (differentiation and formalization), and environmental dynamism, influence ambidexterity, and there is a positive impact of ambidexterity on firm performance."
Keywords: 650; Organizational ambidexterity; Structural approach; Contextual approach; Organizational structure; Environmental dynamism; Firm performance